Klasifikasi Hasil Belajar Peserta Didik Pada Jurusan Teknik Komputer dan Jaringan (TKJ) di SMK Negeri 3 Malang Menggunakan Algoritme Naive Bayes - Ricky Gunawan; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
This research is based on the results of observations and interviews with teachers, the limitations of the teacher in recognizing and analyzing factors that can influence student achievement and student achievement. Based on these conditions, this study aims to use the Naive Bayes algorithm to classify the performance of students from the Department of Computer and Network Engineering at Vocational High School 3 Malang, and to assess the accuracy of Naive Bayes algorithm at the Classification of student performance in the Department of Computer and Network Engineering at SMK Negeri 3 Malang. Research developed based on preliminary research is the classification of performance of students from the Department of Computer and Network Engineering at the vocational school 3 Malang, which is divided into three categories, Very Good, Good and Enough. The student data used in this study are from SMK Negeri 3 Malang students. The data obtained was 63 student attributes used in this study and 10 and 1 attribute for output from the classification. The results of the accuracy test of the training data test using the Naive Bayes classification with differences in the training data showed the results of a fixed accuracy of 70%. For tests with differences in test data, an accuracy of 80% and 70% is displayed with an average accuracy of 75%. On a system that is also applied, the naive bayes classification gets 90% accuracy because all records are used for the training data.